Influence of dipping time on cracking during bending of hot dip galvanized coatings with Sn and Ti contents - V. Di Cocco; L. Zortea (Fracture and Structural Integrity)
In the last years, the attention to environmental topics led a new approach solution in classical protection techniques, introducing innovative way oriented to optimize different coating properties. Hot-dip galvanizing is a classical process aimed to generate coatings on iron-based surfaces, used unchanged since 200 years: some chemical elements are added in the bath with different aims (e.g., Pb is really important for its fluidizing properties, sometimes replaced by Sn) but sometimes these elements are dangerous for human health (e.g. … Pb!). In this work, the influence of dipping time and coatings chemical compositions on damaging micromechanisms was investigated considering different Sn and Ti contents. Main damaging micromechanisms in hot dip zinc coated ipersandelin steel specimens were investigated by means of bending tests. Longitudinal sections of bended specimens were observed by means of a LOM (Light Optical Microscope): main damage micromechanisms were identified as longitudinal and radial cracks.